Synthesis and Biological Evaluation of New N,N′-Bis(1-substituted-ethylidene)-ethane1,2-diamine and Their Acetyl and Trifluoroacetyl Derivatives as Cytotoxic and Antimicrobial Agents - Khalid A. Khan; Hassan M. Faidallah; Abdullah M. Asiri (Journal of Chemistry)
Several Schiff bases 2 have been prepared by the condensation of various methyl ketones 1 with 1,2-ethylenediamine. Subsequent acylation of these Schiff bases with trifluoroacetic anhydride in THF yields the corresponding trifluoroacetyl derivatives 3. However, o-hydroxy- and o-methoxy-substituted derivatives yielded substituted-trifluoromethylchroman-4-ones. Additionally, Schiff bases when reacted with acetic anhydride afforded the C-acetylated derivatives 4. The structures of the isolated compounds were fully determined by spectral methods. Preliminary biological screening of the prepared compounds revealed significant cytotoxic and antimicrobial activities.